Kill zone [videorecording (DVD)] - Ye, Weixin; Yen, Donnie, 1963-; Hung, Samo, 1952-; Yam, Simon (Dragon dynasty (Series), 2006)
An aging and ill cop uses unorthodox tactics to take down the gangster responsible for the kidnapping of his goddaughter.